1986
DOI: 10.1021/om00139a011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and reactivity of [NBu4]+[Pt(III)(C6Cl5)4]-: molecular structures of [NBu4]2+[Pt(C6Cl5)4]2-.cntdot.2CH2Cl2, [NBu4]+[Pt(III)(C6Cl5)4]- and [NBu4]+[Pt(C6Cl5)4(NO)]-

Abstract: 8, V = 5248 (3) %r3, and p(calcd) = 1.85 g cm-3 for 2 = 4. The structure has been refined to a final agreement factor of R = 6.6%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 3 publications
(5 reference statements)
3
29
0
Order By: Relevance
“…Like its Pt II precursor, [Pt III (C 6 Cl 5 ) 4 ] À adopts a square planar geometry. The bond lengths of the Pt III complex (2.094 Å ) and its Pt II precursor (2.086 Å ) are very similar (24). Similar square-planar geometries were observed for [Ir II (C 6 All these complexes proved to be (moderately) air and moisture stable, both as a solid and in solution.…”
Section: B the P-arene-phosphine Rh(ii) Complexessupporting
confidence: 63%
See 2 more Smart Citations
“…Like its Pt II precursor, [Pt III (C 6 Cl 5 ) 4 ] À adopts a square planar geometry. The bond lengths of the Pt III complex (2.094 Å ) and its Pt II precursor (2.086 Å ) are very similar (24). Similar square-planar geometries were observed for [Ir II (C 6 All these complexes proved to be (moderately) air and moisture stable, both as a solid and in solution.…”
Section: B the P-arene-phosphine Rh(ii) Complexessupporting
confidence: 63%
“…4 ] nÀ type complexes have been reported (Fig. 11) (23,24). Magnetic susceptibility values of m eff ¼ 2.57 and 2.42 m B at 260 and 80 K were obtained, which is in agreement with an S ¼ 1 2 spin system with a substantial spin-orbit contribution from mixing with lower lying states.…”
Section: B the P-arene-phosphine Rh(ii) Complexessupporting
confidence: 61%
See 1 more Smart Citation
“…[ SPY-5 2.054(9) 1.141 (14) 119.5(8) [14] [Pt(C 6 F 5 ) 3 (PPhMe 2 )(NO)] (2 c) 1800 [c] SPY-5 2.068(7) 1.086(7) 120.1 (6) SPY-5 2.22(6) 1.04(9) 180 [13] NO(g) 1876 ± ± 1.15 ± [25] NO (g) 2345 ± ± 1.06 ± [25] [a] Estimated standard deviation not reported. (Table 5) which could not be easily anticipated, especially considering the similar electronic effects traditionally assigned to the C 6 F 5 and C 6 Cl 5 groups.…”
Section: Bond Lengthsmentioning
confidence: 99%
“…We had found that the pentachlorophenyl group is a well-behaved ligand allowing a convenient entry to platinum nitrosyl systems. With the synthesis of [NBu 4 ][Pt(C 6 Cl 5 ) 4 (NO)] [13] and [NBu 4 ]-[Pt(C 6 Cl 5 ) 2 Cl 2 (NO)] [14] we obtained examples of both linear and bent platinum nitrosyl species for a same {PtNO} 8 electronic configuration. We report now a combined computational and experimental study of perhalophenyl-nitrosyl derivatives of platinum in order to understand the role of the stabilizing coligands in the bonding mode of the [Pt]±NO unit.…”
Section: Introductionmentioning
confidence: 99%